2017
DOI: 10.18632/oncotarget.18161
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA CCAT2 as a novel biomaker of metastasis and prognosis in human cancer: a meta-analysis

Abstract: Colon cancer-associated transcript2 (CCAT2), a long noncoding RNA (LncRNA), has been found to function as an oncogene in various cancers. However, the clinical value of CCAT2 in cancers remains unclear. Therefore, we performed this meta-analysis to investigate the association between CCAT2 level and metastasis & prognosis in malignant tumors. The meta analysis was performed by using a systematic search in PubMed, Web of Science, and Cochrane Library from inception to NOV 17, 2016. According to the inclusion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…There is increasing evidence that lncRNAs play important roles in the pathogenesis of a variety of cancers, including HCC, and can even serve as prognostic biomarkers (Li et al, ; Wang et al, ; Zhang, Fan, Jian, Chen, & Lai, ). In this study, we found downregulation of CASC2 in HCC compared with adjacent NTTs instead of normal tissues in healthy people.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that lncRNAs play important roles in the pathogenesis of a variety of cancers, including HCC, and can even serve as prognostic biomarkers (Li et al, ; Wang et al, ; Zhang, Fan, Jian, Chen, & Lai, ). In this study, we found downregulation of CASC2 in HCC compared with adjacent NTTs instead of normal tissues in healthy people.…”
Section: Discussionmentioning
confidence: 99%
“…The promising era of cancer diagnosis is greatly developed through the targeted molecules finding . However, TNBC’s targeted therapy cannot be performed until now since its absence of PR, ER and HER2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The promising era of cancer diagnosis is greatly developed through the targeted molecules finding. 8,26 However, TNBC's targeted therapy cannot be performed until now since its absence of PR, ER and HER2 expression. So, searching for novel target tightly co-related with progression of TNBC is of great significance for its diagnosis and therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies are evident that CCAT2 promotes chromosomal instability, cellular progression and tumor metastasis in various kinds of cancer such as colon [28], lung cancer [72] breast cancer [73], gastric cancer [74], ovary can-Open Journal of Obstetrics and Gynecology cer [75] and cervical cancer [30]. Knockdown of CCAT2 inhibited the cell development, growth and promoted cell death [29]. CCAT2 upregulates MYCregulated miRNA-17-5p and miRNA-20a responsible for cellular proliferation, chromosomal modifications, and metastasis in many cancers via [76].…”
Section: Ccat2mentioning
confidence: 99%